Increasing Digital Literacy in Realizing Golden Indonesia - Alfriansa Agustina; Anggara Setya Saputra; Devit Bagus Indranika; Suryoto; Oti Kusumaningsih; Johar Mamuri; Emiraldo Win Pazqara (PT FORMOSA CENDEKIA GLOBAL, 2022)
It is diaccompanied by the condition of Indonesia where the literature movement in the ability of students to read in the world of education and society is still relatively minimal. One that can be done through the school literacy movement is one form of government awareness of the importance of building a culture of literacy in the world of education in order to create a culture of reading and writing in the school environment as an effort to realize lifelong education. The main and most basic activities are directed at increasing interest in reading. The values of character education can be conveyed implicitly in every learning process, especially in Indonesian language learning. The use of digital literacy is also able to lead students to be able to capture and retrieve information from the internet with teacher monitoring. It is able to broaden students horizons in taking knowledge broadly and facilitate students to be creative freely with maximum monitoring and supervision.